Long-term obstetric, perinatal, and surgical complications in singleton pregnancies following previous cesarean myomectomy: a retrospective multicentric study - Güler, Oğuz; Hatırnaz, Şafak; Sparic, Radmila; Basbug, Alper; Erol, Onur; Kalkan, Üzeyir; Ulubaşoğlu, Hasan; Trojano, Giuseppe; Ürkmez, Sebati Sinan; Tinelli, Andrea (Frontiers in Surgery, 2024)
Objectives: The safety of cesarean myomectomy has been proven by previous studies. Our study aimed to reveal the long-term perinatal, obstetric and surgical outcomes of cesarean myomectomy (CM) by comparing the different CM techniques. Material and Methods: Our study is a retrospective multicentric case-control study involving 7 hospitals. 226 singleton pregnancies that underwent repeated cesarean section (CS) between 2015 and 2020 were included in the study. In previous pregnancies, 113 of 226 cases had CM (Group A) and 113 had only CS (Group B). Of the 113 cases in which CM was performed, endometrial myomectomy (EM) as Subgroup A1, was performed in 58 and serosal myomectomy (SM) as Subgroup A2 was performed in 55. The groups were compared in terms of obstetric, perinatal and surgical outcomes; and fibroid recurrence, myomectomy scar healing rate and adhesion formation were noted. Results: There was no significant difference between the groups in terms of maternal age, body mass index, gravidity, parity and fibroid diameter in previous CS (p>0.05). In the perinatal and obstetric evaluation of the groups; there was no significant difference between the groups in terms of neonatal weight, Apgar score, fetal growth restriction, preterm premature rupture of membranes, preterm delivery, hypertension in pregnancy and diabetes mellitus (p>0.05). Fibroid recurrence rate was determined as 28.3% and myomectomy scar good healing rate was 99.1%. There was no difference between the groups in terms of CS duration, preoperative and postoperative hemoglobin levels, perioperative blood transfusion rates, febrile morbidity and prolonged hospitalization(p>0.05). In terms of adhesion formation, although the adhesion rate of the SM group was higher than that of the EM group, no statistically significant difference was detected between the groups. Conclusion: This study showed that in pregnancies following CM, obstetrical, perinatal, and surgical outcomes were unaffected. Obstetricians can safely use CM, either the trans-endometrial or serosal technique, as it is a safe and effective method with long-term results.